Balkan Legacies of the Great War: The Past is Never Dead - Anastasakis, Othon; Madden, David; Roberts, Elizabeth; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
.
1. Introduction: The Past Is Never Dead$1! =(B; Othon Anastasakis, David Madden and Elizabeth Roberts -- 2. Too Much History and Too Many Neighbours: Europe and The Balkans Before 1914; Margaret MacMillan -- 3. The Black Hand and the Sarajevo Conspiracy; Ivor Roberts -- 4. The Contrasting Legacies of the South Slav Question;Ivo Banac -- 5. Was The First World War The Turning Point at which Bulgarian History Failed to Turn?; Richard Crampton -- 6. World War I and The Fall Of The Ottomans: Consequences for South East -- Europe; Eugene Rogan -- 7. Unwanted Legacies: Greece and the Great War; Basil C. Gounaris -- Epilogue: $1! = (BIt Is Not Even Past!; Othon Anastasakis, David Madden, and Elizabeth Roberts. .s
Keywords: History; History, Modern; Europe -- History; Military history; History; History of Military; European History; Modern History; Electronic books